2006
DOI: 10.1016/j.ccr.2006.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of HIF-1α and HIF-2α to common target genes is differentially regulated in neuroblastoma: HIF-2α promotes an aggressive phenotype

Abstract: In neuroblastoma specimens, HIF-2alpha but not HIF-1alpha is strongly expressed in well-vascularized areas. In vitro, HIF-2alpha protein was stabilized at 5% O2 (resembling end capillary oxygen conditions) and, in contrast to the low HIF-1alpha activity at this oxygen level, actively transcribed genes like VEGF. Under hypoxia (1% O2), HIF-1alpha was transiently stabilized and primarily mediated acute responses, whereas HIF-2alpha protein gradually accumulated and governed prolonged hypoxic gene activation. Kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
598
4
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 645 publications
(669 citation statements)
references
References 56 publications
61
598
4
6
Order By: Relevance
“…Interestingly, HIF-2a has been shown to enhance aggressive tumor behavior (Kondo et al, 2003;Holmquist-Mengelbier et al, 2006). This is consistent with HIF-2a-dependent regulation of TWIST1 as shown here.…”
Section: Twist1 Is a Target Of Hif-2a Eh Gort Et Alsupporting
confidence: 90%
“…Interestingly, HIF-2a has been shown to enhance aggressive tumor behavior (Kondo et al, 2003;Holmquist-Mengelbier et al, 2006). This is consistent with HIF-2a-dependent regulation of TWIST1 as shown here.…”
Section: Twist1 Is a Target Of Hif-2a Eh Gort Et Alsupporting
confidence: 90%
“…With neuroblastoma as a model system, we showed that during hypoxia-driven VEGF expression there is a temporal shift in the usage of the HIFs; whereas the VEGF expression is HIF-1 dependent at an acute phase, the expression during prolonged hypoxia is primarily HIF-2 driven (Holmquist-Mengelbier et al 2006). In a follow-up study using a large clinical neuroblastoma tissue microarray material immunohistochemically stained for HIF-1α, HIF-2α, VEGF and blood vessel endothelial cells (CD31), tumor cells staining intensely for HIFs correlated to VEGF positivity, while the HIF-1α and HIF-2α staining did not fully correlate to each other ).…”
Section: Hifs and Vascularizationmentioning
confidence: 94%
“…In tumor cell lines, with few exceptions both HIF-1α and HIF-2α are expressed, and we recently postulated that HIF-1α is involved in adaptation to acute, and HIF-2α to prolonged, hypoxia (Holmquist-Mengelbier et al 2006;Helczynska et al 2008). For historical reasons, HIF-1α is the isoform that has been most extensively studied in clinical tumor materials and frequently been correlated with aggressive tumor disease, but in recent years high tumor levels of HIF-2α rather than HIF-1α have been shown to associate with negative overall survival and metastatic disease.…”
Section: Hypoxia In Solid Tumors and Relation To Tumor Aggressivenessmentioning
confidence: 99%
See 2 more Smart Citations